Approaching the Discriminatory Work Environment as Stressor: The Protective Role of Job Satisfaction on Health - Di Marco, Donatella; López-Cabrera, Rocio; Arenas, Alicia; Giorgi, Gabriele; Arcangeli, Giulio; Mucci, Nicola (Frontiers in Psychology, 2016)
Discrimination is a complex phenomenon with adverse consequences at personal and organisational levels. Past studies have demonstrated that workers who are victims of discrimination might show less job satisfaction, less organisational commitment and worse levels of health and productivity. Although most research has focused on the effects of discrimination on victims, less is known about the extent to which discrimination produces consequences on workers who perceive the existence of a discriminatory work environment. The goal of this article is to analyse the consequences of the perception of a discriminatory work environment on employees’ health. The importance of this relationship is studied taking into account the mediating effect of job satisfaction. In order to reach this goal a cross-sectional study was carried out with a sample of 1633 Italian workers (male= 826, female= 764), employed in private and public sectors, and in different hierarchical positions. Results suggest that the perception of a discriminatory work environment is negatively associated with employees’ health. This relationship is partially mediated by job satisfaction (R²= .17). This study demonstrates that perceiving a discriminatory work environment might have a negative impact on workers’ health. A higher level of job satisfaction might buffer this effect. These findings have several practical implications. On the one hand, Human Resource Managers need to intervene in order to recognise and diminish implicit biases, creating a healthy and inclusive environment (e.g. through training, diversity policies, etc.). On the other hand, promoting job satisfaction (e.g. providing mechanisms of voice) might help workers to preserve their well-being, coping with the negative effects of a discriminatory work environment. Keywords: Discriminatory work environment, Job satisfaction, Employees’ health, Human Resource Management, Italian workers, Workplace, Work-related stress, Occupational medicine